Diffuse-Type Tenosynovial Giant Cell Tumor of the Knee with Concurrent Polymicrobial Infection (Klebsiella oxytoca and Group B Streptococcus). (14th August 2021) - Marshall, J. Hunter; Skedros, John G.; Campana, Chris F.; Seibert, Allan M.
Abstract : Tenosynovial giant cell tumors (TGCT) are a rare class of benign proliferative tumors that are classified according to their presentation: localized-type (L-TGCT) or diffuse-type (D-TGCT). TGCT is synonymous with pigmented villonodular synovitis (PVNS). We describe the unique case of a 56-year-old obese male with type 2 diabetes who had polymicrobial septic arthritis of his left knee joint with concurrent D-TGCT in the same knee. While on a vacation, he noticed spontaneous left knee pain and swelling with an acute onset of fever. He was diagnosed with septic arthritis that was attributed to hematogenous spread from a leg laceration. The septic arthritis was treated with arthroscopic lavage and debridement, including simultaneous excision of the D-TGCT lesions, followed by intravenous ceftriaxone. Cultures of the synovial tissue that were obtained during arthroscopy grew Klebsiella oxytoca and beta-hemolytic (group B) Streptococcus agalactiae. We were not able to find another reported case of any joint with (1) a polymicrobial bacterial infection that included Klebsiella oxytoca and (2) concurrent bacterial septic arthritis and TGCT.